Financial Management of Health Services in Improving Efficiency and Service Quality: A Systematic Literature Review - Nadia Dwi Wulandari; Nanda Sincilia; Dwi Noerjoedianto; Arnild Augina Makarisce (International Journal of Health Engineering and Technology, 2026)
Financial management in health services plays a crucial role in improving efficiency and service quality,particularly in the context of limited resources and the implementation of national health financing systems.This study aims to analyze the role of health service financial management in enhancing efficiency and qualityof care through a systematic literature review approach. Articles were identified using Google Scholar with apublication period from 2020 to 2025. Of the 200 articles initially identified, a screening and eligibility processbased on inclusion and exclusion criteria resulted in 10 relevant articles for analysis. The findings indicate thateffective financial management through budget planning, cost control, health economic evaluation, andoptimization of health financing systems such as the National Health Insurance contributes to improvedoperational efficiency and service quality. In addition, strong financial performance and managerialinnovations, including digitalization, support improvements in service processes and outcomes. This reviewconcludes that integrated and performance-based financial management is a strategic factor in achievingefficient, high-quality, and sustainable health services.